Motivation for postgraduate studies by nonacademic optometrists: A case study at a South African university - Rekha Hansraj; Nishanee Rampersad (AOSIS, 2022)
Background: An increasing number of optometrists who are nonacademics are pursuing postgraduate studies, despite such qualifications traditionally being more relevant to an academic rather than a clinical setting. Aim: This study set out to explore possible reasons for the increase in postgraduate studies by nonacademic optometrists and their experiences thereof. Setting: Postgraduate optometry students who were registered at a selected South African university within the period 2010-2020 participated in the study. Methods: A descriptive cross-sectional research design was used, which entailed an online survey and a follow-up questionnaire focused on the motivation for postgraduate studies, choice of institution, research area, expectations and outcomes and supervision received. Convenience sampling was used to recruit the participants, and data were analysed with descriptive statistics. Results: Responses were received from 54 optometrists who were pursuing postgraduate studies but not currently in academia. The main reasons reported for enrolling in postgraduate studies were interest in research (69.2%) and academia (61.5%). Institutional reputation was the reason provided by 48.1% of respondents for their choice of institution for their postgraduate studies. Fifty per cent of respondents opted for research in the public health field. To be a better researcher was the most common expectation (88.5%), with 73.1% indicating achieving this outcome. Most respondents indicated that they had received constructive and timeous supervision during their studies. Conclusion: Interest in research and academia are important factors influencing nonacademic optometrists to pursue postgraduate studies; however, the postgraduate experience is likely to also facilitate development of other professional and clinical skills. Contribution: This study provides an insight into the motivation and experiences of non academic optometrists who pursue postgraduate degrees.